ANALYSIS OF TRANSLATION ERRORS IN GOOGLE TRANSLATE ARABIC TEXTS INTO INDONESIAN IN THE BOOK IHYA' ULUMUDDIN - M. Alaika Nasrullah; Anyes Lathifatul Insaniyah; Mauliddah Khasanah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This research aims to identify the errors of Google Translate in translating Arabic text into Indonesian in the book Ihya' Ulumudin, specifically in the fields of syntax and semantics. The type of research used in this study is library research, which is a data collection technique involving a review of books related to the problem to be solved. The data used in this study is from the book